2020
DOI: 10.7554/elife.47333
|View full text |Cite
|
Sign up to set email alerts
|

Telomere dysfunction cooperates with epigenetic alterations to impair murine embryonic stem cell fate commitment

Abstract: The precise relationship between epigenetic alterations and telomere dysfunction is still an extant question. Previously, we showed that eroded telomeres lead to differentiation instability in murine embryonic stem cells (mESCs) via DNA hypomethylation at pluripotency-factor promoters. Here, we uncovered that telomerase reverse transcriptase null (Tert-/-) mESCs exhibit genome-wide alterations in chromatin accessibility and gene expression during differentiation. These changes were accompanied by an increase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 117 publications
(137 reference statements)
2
14
0
Order By: Relevance
“…In addition, the expression of LIN28A also decreased in FD‐ treatment, while its expression increased significantly in F‐, indicating that it was also regulated by other factors. In previous study, OCT4 and LIN28A were also influenced by additional factors or chromatin conformation, such as H3K27ac or H3K4me 2,67,68 . Our study demonstrated that both were inhibited by H3K9me2 during pluripotency maintenance in piPSCs.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, the expression of LIN28A also decreased in FD‐ treatment, while its expression increased significantly in F‐, indicating that it was also regulated by other factors. In previous study, OCT4 and LIN28A were also influenced by additional factors or chromatin conformation, such as H3K27ac or H3K4me 2,67,68 . Our study demonstrated that both were inhibited by H3K9me2 during pluripotency maintenance in piPSCs.…”
Section: Discussionsupporting
confidence: 63%
“…The exact relationship between telomere attrition and epigenetic alterations is still elusive. However, some evidence suggests that eroded telomeres lead to differentiation instability via DNA methylation ( Criqui et al, 2020 ).…”
Section: Telomere Length and Epigenetic Signatures As The Predictors Of Biological Agementioning
confidence: 99%
“…Normally, somatic cells have a limited proliferation capacity due to the shortening of telomeres (repetitive protective sequences located at the ends of chromosomes). In cancer cells, telomere attrition is partially prevented thanks to the addition of telomeric repeats by the enzyme telomerase, whose catalytic core is composed of a reverse transcriptase (TERT) and an RNA template [ 155 ]. Mutations in the TERT promoter are found in 60–80% of GBMs and have been associated with increased telomerase activity (TA).…”
Section: Epigenetic Aspects Of the Gscs Plasticitymentioning
confidence: 99%